Feline tetherin efficiently restricts release of feline immunodeficiency virus but not spreading of infection - Dietrich, Isabelle; McMonagle, Elizabeth L; Petit, Sarah J; Vijayakrishnan, Swetha; Logan, Nicola; Chan, Chi N; Towers, Greg J; Hosie, Margaret J; Willett, Brian J (Journal of virology, 2011)
Domestic cats endure infections by all three subfamilies of the retroviridae: lentiviruses (feline immunodeficiency virus [FIV]), gammaretroviruses (feline leukemia virus [FeLV]), and spumaretroviruses (feline foamy virus [FFV]). Thus, cats present an insight into the evolution of the host-retrovirus relationship and the development of intrinsic/innate immune mechanisms. Tetherin (BST-2) is an interferon-inducible transmembrane protein that inhibits the release of enveloped viruses from infected cells. Here, we characterize the feline homologue of tetherin and assess its effects on the replication of FIV. Tetherin was expressed in many feline cell lines, and expression was induced by interferons, including alpha interferon (IFN-α), IFN-ω, and IFN-γ. Like human tetherin, feline tetherin displayed potent inhibition of FIV and HIV-1 particle release; however, this activity resisted antagonism by either HIV-1 Vpu or the FIV Env and "OrfA" proteins. Further, as overexpression of complete FIV genomes in trans could not overcome feline tetherin, these data suggest that FIV lacks a functional tetherin antagonist. However, when expressed stably in feline cell lines, tetherin did not abrogate the replication of FIV; indeed, syncytium formation was significantly enhanced in tetherin-expressing cells infected with cell culture-adapted (CD134-independent) strains of FIV (FIV Fca-F14 and FIV Pco-CoLV). Thus, while tetherin may prevent the release of nascent viral particles, cell-to-cell spread remains efficient in the presence of abundant viral receptors and tetherin upregulation may enhance syncytium formation. Accordingly, tetherin expression in vivo may promote the selective expansion of viral variants capable of more efficient cell-to-cell spread.